Computational analysis of the influence of wing flow on the horizontal stabilizer - Silveira, Arthur Inácio Santos; Guimarães, Guilherme Henrique Moura; Mariano, Felipe Pamplona (Brazilian Journal of Production Engineering, 2025)
In the context of aircraft design, especially in competitions such as SAE AeroDesign, CFD simulations are essential to predict the flow behavior around aerodynamic surfaces, contributing to improving aircraft efficiency. This study analyzed the relative position between the wing and the horizontal stabilizer of an aircraft in three wing-tail assembly configurations, evaluating the impacts of the vertical and horizontal displacement of the tail on the lift, drag and moment coefficients. The methodology employed used four free software programs: FreeCAD for the geometric modeling of the CH10SM and NACA 0012 airfoils, Salome-Meca® for the generation of unstructured meshes, OpenFOAM® for simulations and ParaView for post-processing. The analysis of the vorticity fields revealed, qualitatively, the configuration that minimizes the interference of the wing flow over the tail, and the evaluation of the aerodynamic coefficients confirmed, quantitatively, that the configuration positioned outside the vortex wake presented the best results. The approach with unstructured meshes and free software proved to be effective and accessible for aerodynamic simulations, with a direct impact on aircraft development.
Keywords: Wing-tail configuration; OpenFOAM; ParaView; SAE AeroDesign; Education